Recipient participation in conversations involving participants with fluent or non-fluent aphasia - Laakso Minna; Godt Sisse (TAYLOR & FRANCIS INC, 2022)
The present study compares the ways in which conversational partners manage expressive linguistic problems produced by participants with fluent vs. non-fluent aphasia. Both everyday conversations with family members and institutional conversations with speech-language therapists were examined. The data consisted of 110 conversational sequences in which the conversational partners addressed expressive aphasic problems. Most problems of the speaker with fluent aphasia were locally restricted phonological and word-finding errors, which were immediately repaired. In contrast, the sparse expression of the speaker with non-fluent aphasia was co-constructed by conversational partners in long negotiation sequences to establish shared understanding. Some differences between recipient participation in everyday and institutional conversation were found. The results emphasise the relevance of the nature of the expressive linguistic problems on participation in interaction. They also add to the clinical knowledge of handling aphasic problems in conversation. This knowledge can be used for developing interaction-focused intervention.